Intravenous glucagon like peptide-1 infusion does not affect dry matter intake or hypothalamic mRNA expression of neuropeptide Y, agouti related peptide and proopiomelanocortin in wethers - Relling, Alejandro Enrique (2014)
The objectives of the present study were to determine the effects of jugular vein infusions of glucagon like peptide-1 (GLP-1) and dietary fat inclusion on dry matter intake, nutrient digestibility and hypothalamic mRNA concentration of neuropeptide Y, agouti related peptide, and proopiomelanocortin in growing sheep. Thirty-six wethers were used (40.7±3.3 kg BW). Treatments were a control diet (n=11), dietary addition (6% of dry matter) of Ca salts of palm oil fatty acids (n=12), or 6-d jugular vein infusions of 0.155 µg kg-1 body weight/day of GLP-1 (n=11). Hormone concentrations were measured in jugular vein plasma from samples taken on days 1, 4 and 6. On day 7, the wethers were slaughtered for hypothalamus collection to measure mRNA concentration. The dietary addition of 6% of Ca salts of palm oil increased plasma GLP-1 concentration (P<0.01) and decreased dry matter intake on day 1, but not on day 6 (time×treatment interaction, P<0.05). The infusion of GLP-1 did not change dry matter intake (P>0.20), but increased neutral detergent fibre digestibility (P<0.01). In conclusion, glucagon like peptide-1 infusion or feeding fat did not decrease dry matter intake or affect hypothalamic neuropeptide mRNA concentrations of sheep.